Assessment of the application for renewal of authorisation of Calsporin® (Bacillus subtilis DSM 15544) for chickens for fattening. (20th July 2018) - ,; Rychen, Guido; Aquilina, Gabriele; Azimonti, Giovanna; Bampidis, Vasileios; Bastos, Maria de Lourdes; Bories, Georges; Chesson, Andrew; Cocconcelli, Pier Sandro; Flachowsky, Gerhard; Gropp, Jürgen; Kolar, Boris; et al.
Abstract: Calsporin ® is the trade name for a feed additive based on Bacillus subtilis DSM 15544. It is currently authorised for use in chickens for fattening, weaned piglets, chickens reared for laying, turkeys, minor avian species and other ornamental and game birds, and ornamental fish. This opinion concerns the renewal of the authorisation of Calsporin ® as a zootechnical additive for chickens for fattening. In 2006 and 2007, the EFSA Panel on Additives and Products or Substances used in Animal Feed (FEEDAP) adopted two opinions on the safety and efficacy of Calsporin ® when used in chickens for fattening, and the active agent was further characterised in an opinion from 2015. The applicant has provided data demonstrating that the additive currently in the market complies with the conditions of authorisation. Furthermore, according to the information provided in the technical dossier, no new evidence has been identified that would make the FEEDAP Panel reconsider the previous conclusions on the safety of the additive. The FEEDAP Panel confirms its previous conclusion that Calsporin ® is safe for the target species, consumers of products from animals fed the additive, users and the environment.